2019
DOI: 10.1111/mmi.14205
|View full text |Cite
|
Sign up to set email alerts
|

Aurantimycin resistance genes contribute to survival of Listeria monocytogenes during life in the environment

Abstract: Summary Bacteria can cope with toxic compounds such as antibiotics by inducing genes for their detoxification. A common detoxification strategy is compound excretion by ATP‐binding cassette (ABC) transporters, which are synthesized upon compound contact. We previously identified the multidrug resistance ABC transporter LieAB in Listeria monocytogenes, a Gram‐positive bacterium that occurs ubiquitously in the environment, but also causes severe infections in humans upon ingestion. Expression of the lieAB genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 53 publications
4
34
0
Order By: Relevance
“…The data presented here suggest an explanation for the common detection of mutations in the sigB operon of L. monocytogenes (28,(33)(34)(35)(36)55), including an earlier study in our own laboratory where an rsbV missense mutation arose during routine subculture (31).…”
Section: Emergence Of Mutated Alleles Within the Sigb Operonmentioning
confidence: 53%
See 2 more Smart Citations
“…The data presented here suggest an explanation for the common detection of mutations in the sigB operon of L. monocytogenes (28,(33)(34)(35)(36)55), including an earlier study in our own laboratory where an rsbV missense mutation arose during routine subculture (31).…”
Section: Emergence Of Mutated Alleles Within the Sigb Operonmentioning
confidence: 53%
“…The occurrence of sigB operon mutations in this study and in other studies (28,31,(33)(34)(35)(36) prompted us to investigate whether undocumented premature stop codons (PMSCs) might be present in the sigB operon in genome sequences deposited in public databases, so we searched for PMSCs in the sigB operon among 22,340 of L. monocytogenes genome assemblies. The PMSC rate per 100 bp (expressed as a % rate per 100 bp to normalise for gene length) for genes in the sigB operon that positively affect σ B activity (rsbV, rsbT and rsbU) was considerably higher than for genes that act negatively (rsbW and rsbX).…”
Section: Loss Of Rsbx Results In Reduced Competitivenessmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, we demonstrated that this efflux pump is expressed when L . monocytogenes comes into contact with aurantimycin A 21 , a depsipeptide antibiotic with very potent bactericidal activity against Gram-positive bacteria and produced by soil-dwelling Streptomyces aurantiacus 22 . Thus, LftR and LieAB likely promote survival of L .…”
Section: Introductionmentioning
confidence: 99%
“…monocytogenes when it comes in contact with S . aurantiacus in the soil, its natural reservoir 21 , from where it may eventually enter the food chain.…”
Section: Introductionmentioning
confidence: 99%